Les territoires du football en Tunisie (1906-2015) - Ali Langar; Myriam Baron; Claude Grasland (EchoGéo)
Before the Soccer World Cup in Russia in June and July 2018, the newspaper Le Monde underlined in March that Tunisians seemed less attached to their national team than to the main clubs evolving in the championship of first division. This leads to be interested in the way this sport became established and spread during the French protectorate, the political role which it played whether it is in the walking towards the independence or, more recently, during the big demonstrations of the revolution of jasmine during winter 2010-2011. Finally, the soccer, the first sport in Tunisia by the number of graduates, leans but also contributes partially to maintain main territorial disparities between the coast and the inside, the North and the South by the setting-up of the main teams participating in the most prestigious championship, that of the First League. However, when are taken into account the regional Leagues, we have to admit that this sport also plays a notable role in the manners among which the arrangement and the rebalancings within the national territory can be arrested.